ANALISIS KEBIJAKAN KEUANGAN SEBAGAI MITIGASI OVERINVESTMENT TERHADAP PROFITABILITAS PERUSAHAAN - Saputra, Muhammad Haris; Fitriaty, Fitriaty; Firmasari, Puja; Mardiana, Mardiana (Jurnal Ilmiah Ekonomi Bisnis, 2024)
The main objective of this study is to analyze the impact of overinvestment on firm performance and the moderating role of debt policy, dividend policy in reducing the negative effect of overinvestment on firm performance. This study uses data from a sample of 50 non-financial companies that have debt and consistently pay dividends from 2010 to 2023. Overinvestment is calculated through two methods: the residual value of the new investment equation and the Hodrick-Prescott (HP) filter. The data was then transformed into panel data, and various models such as fixed effect, random effect, and common effect were applied to identify the most appropriate model. This study found a negative correlation between overinvestment and firm performance. Debt policy is a mitigating factor in overcoming agency conflicts and reducing the negative impact of overinvestment on firm performance. Dividend policy is proven effective in reducing the negative impact of overinvestment by limiting excess cash. The combination of debt and dividend policy is identified as a comprehensive strategy to mitigate overinvestment, as it helps limit excessive free cash flow. This combination also lowers financing funds to a minimum level that could potentially lead to a shortage of funds for profitable projects in the future. Careful calculations are required to ensure the company achieves a balance, avoiding the neglect of profitable investments in the future.